Perlindungan Hukum Bagi Kreditur Serta Legalitas Penahanan Jaminan Oleh Kreditur: Studi Kasus Putusan Mahkamah Agung No 1733 K/PDT/2014 - Amalia, Selma Dwi; Maula, Putri Ni’matul; Firdaus, Muhammad Bintang; Purnama, Rendika; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Credit agreements as principal agreements are often followed by additional agreements such as collateral, which are interrelated in their implementation. This study aims to analyze the legal relationship between the principal agreement (credit agreement) and additional agreement (collateral) and the legality of collateral retention by creditors in the case of Supreme Court Decision No. 1733 K/Pdt/2014. The background of this study is based on a dispute between debtors and creditors regarding default, debt collection that is not in accordance with the agreement, and retention of collateral certificates without a clear legal basis. The research method used is a normative legal approach with an analysis of legal documents and court decisions. The results of the study indicate that credit agreements as principal agreements have direct implications for the validity of additional agreements, especially in terms of collateral execution. The Supreme Court ruled that the creditor's action of withholding collateral without a legal basis violated the principles of contract law, so that some of the debtor's demands were granted. In conclusion, this case emphasizes the importance of transparency and balance of rights and obligations in credit agreements to ensure legal certainty for the parties.